1986
DOI: 10.1136/hrt.56.5.433
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal, global, and regional haemodynamic responses to a vascular antagonist of vasopressin in patients with congestive heart failure with and without hyponatraemia.

Abstract: The pathophysiological role of an increase in circulating vasopressin in sustaining global and regional vasoconstriction in patients with congestive heart failure has not been established, particularly in patients with hyponatraemia. To assess this further, 20 patients with congestive heart failure refractory to digoxin and diuretics were studied before and 60 minutes after the intravenous injection (5 micrograms/kg) of the vascular antagonist of vasopressin [1(beta-mercapto-beta,beta-cyclopentamethylene-propi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

1987
1987
2007
2007

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Pharmacological blockade of AVP receptors has therefore become an attractive method of improving symptomatology and functional class in adults with heart failure. 8,[11][12][13] To date, very limited data exist on secretion of AVP in infants and children with heart failure. 14 The purpose of the present study was to determine whether AVP levels are elevated in children with CHF attributable to left ventricular dysfunction or symptomatic pulmonary overcirculation attributable to large left-to-right intracardiac shunts and to determine whether AVP levels correlate with functional clinical status in patients with ventricular dysfunction.…”
mentioning
confidence: 99%
“…Pharmacological blockade of AVP receptors has therefore become an attractive method of improving symptomatology and functional class in adults with heart failure. 8,[11][12][13] To date, very limited data exist on secretion of AVP in infants and children with heart failure. 14 The purpose of the present study was to determine whether AVP levels are elevated in children with CHF attributable to left ventricular dysfunction or symptomatic pulmonary overcirculation attributable to large left-to-right intracardiac shunts and to determine whether AVP levels correlate with functional clinical status in patients with ventricular dysfunction.…”
mentioning
confidence: 99%
“…Unfortunately, although these agents antagonized pressor and antidiuretic responses in animals, they were found to have a paradoxical weak agonism in humans (Verbalis et al 2002). In addition, these compounds had short biological half‐lives and poor oral bioavailability (Nicod et al 1985; Verbalis et al 2002). In 1991, the first nonpeptide AVP receptor antagonist was discovered in Japan (Yamamura et al 1991).…”
Section: Arginine Vasopressin Antagonistsmentioning
confidence: 99%
“…Consequently, specific antagonists of the vascular effects of AVP have been developed and used in CHF. As yet there are no reports of attempts to block the renal effects of AVP in CHF (Creager et al 1986;Nicod et al 1986). …”
Section: Antidiuretic Hormone (Arginine Vasopressin)mentioning
confidence: 99%
“…Consequently, specific antagonists of the vascular effects of AVP have been developed and used in CHF. As yet there are no reports of attempts to block the renal effects of AVP in CHF (Creager et al 1986;Nicod et al 1986). Dzau et al (1984) have reported that the metabolites of the prostaglandins PGI2 and PGEz in patients with CHF reach 3-10 times the levels of those found in normal subjects.…”
Section: Antidiuretic Hormone (Arginine Vasopressin)mentioning
confidence: 99%